Initial [18F]FDG PET/CT in high-risk DTC patients - Ruhlmann, Marcus; Binse, Ina; Bockisch, Andreas; Rosenbaum-Krumme, Sandra J. (Nuklearmedizin - NuclearMedicine, 2016)
In a previous paper, we published the impact of initial [18F]FDG PET/CT (FDG-PET/CT) in high-risk patients with differentiated thyroid cancer (DTC) and described the changes in therapy management. The aim of the present study was to evaluate the prognostic impact of the initial FDG-PET/CT on a patient’s follow-up over three years and the rate of complete remission. Patients, methods: This study included 109 DTC patients who underwent radioiodine treatment (RIT), including posttherapeutic whole-body scintigraphy with FDG-PET/CT and a follow-up over three years. The follow-up included high-resolution sonography of the neck and determination of serum Tg as well as Tg antibodies every six months. The results of initial FDG-PET/CT and whole-body scintigraphy were compared with the status after three years of follow-up. Results: 24/109 patients (22%) presented FDG-positive lesions, 22/109 patients (20%) only iodine-positive lesions, and 63/109 patients (58%) neither FDG-positive nor iodine-positive lesions. After three years, 83/109 patients (76%) revealed full remission, 15/109 patients (14%) tumour persistence and 11/109 patients (10%) a progressive disease. The negative predictive value (NPV) was calculated for patients without FDG-positive lesions (NPV 85%) and patients without any lesions (NPV 91%) regarding full remission in the follow-up. Conclusion: FDG-PET/CT has a high NPV (85% to 91%) in DTC patients regarding recurrence-free follow-up after three years. The change in patient management in patients with iodine-negative lesions can lead to a higher rate of full remissions in the follow-up after additional surgery. Therefore, FDG-PET/ CT should be performed in all high-risk DTC patients in the context of the first RIT to improve patient management and risk stratification.
Keywords: Differentiated thyroid cancer; FDG-PET/CT; thyroid cancer; follow-up; iodine negative; radioiodine therapy